Peran Budaya Organisasi dalam Meningkatkan Kinerja Pegawai pada Lembaga Pemerintah - Erma Widyastuti; Nisrina Akbar Rizky Putri (Universitas Muhammadiyah Klaten, 2025)
This study aims to analyze the influence of organizational culture on employee performance in a government institution. Organizational culture is considered an important factor that can create a productive work environment and support the achievement of institutional goals. This research uses a quantitative approach through a survey technique involving 60 employees selected using purposive sampling. The research instrument was a Likert scale questionnaire that had been tested for validity and reliability. The results showed that organizational culture has a positive and significant influence on employee performance, with a regression coefficient of 0.625 and an R Square value of 0.391. These findings indicate that organizational culture explains 39.1% of the variation in employee performance. This study emphasizes the importance of strengthening organizational culture to enhance the effectiveness and performance of employees in the public sector.